Flogging sexual transgression: Interrogating the costs of the 'Fifty Shades effect'. (December 2013) - Dymock, Alex
This article offers a critical reading of the Fifty Shades phenomenon by situating the novels as works of transgressive erotic fiction that stimulate circuits of female consumption and the production of sexual identity as commodity. It submits a novel contribution to current scholarship on the mechanisms of sexual transgression by acknowledging its neutral or even reactive qualities, and by laying bare its relationship with disciplinary regimes of social power. It demonstrates that, rather than a politically progressive utopian strategy that might delimit the parameters of sexual desire, transgression now primarily functions as a mechanism through which capitalism is reinforced and the institutions of heteronormativity maintained.